Comparison of the Trapezoidal Rule and Simpson's Rule in the Riemann-Liouville Fractional Integral Approach - Muslihin, Khoirunnisa Rohadatul Aisy; Fauziyah, Wida Nurul; Purwani, Sri (Operations Research: International Conference Series, 2022)
Research on calculus has developed a lot, including fractional calculus. Fractional calculus is a branch of mathematics that transforms the orders of derivatives and integrals into rational or even real values. In finding the value of the derivative and the fractional integral, a numerical method is needed to find it, because of the difficulty if it is done using an analytical method. In this paper, we will describe the Riemann-Liouville fractional integral approach using the trapezoidal rule and Simpson's rule. We also provide an overview of the comparisons and errors that result from the two methods.Â